Evaluation of Antagonistic Plant Materials to Control Southern Root Knot Nematode in Tomato - Kafle, Arun (Journal of Agriculture and Environment, 2013)
Marigold ((Tagetes patula), crotalaria (Crotalaria juncia), rapeseed plant (Brassica rapa) and oat (Avena sativa) as antagonistic plant and tomato (Lycopersicon esculentum), CL1104 variety as control, were evaluated to determine the effect on southern root knot nematode population in pot experiment at Tsukuba, Japan in year 2010. Completely Randomized Design (CRD) with three replications was used. Initial juvenile population was 30.0±2.8 per 20g soil. The juvenile nematode population was counted 63 days after transplanting and biomass of plants was incorporated in soil. Population was again counted 11 days and 13 day after biomass incorporation. At final count of Juvenile nematode population, it was found highest in tomato (66.6 /20g soil). Highest control was achieved in marigold (2.3 juvenile/20g soil) followed by crotalaria (3.0 juvenile/20g soil. Marigold and crotalaria followed by oat in rotation with tomato were observed as best antagonist plants to control Southern root knot nematode.